Possibilities of simultaneous voltammetric detection of tocopherols in non-aqueous media - Jashari, Granit; Sýs, Milan; Metelka, Radovan; Švancara, Ivan (BEST Servis, 2019)
An electrochemical study on possibilities of simultaneous detection of tocopherols based on their anodic oxidation at various electrode materials in non-aqueous supporting electrolytes was performed. Several working conditions, such as selection of working electrode, supporting electrolyte, effect of surfactant, water content and parameters of square-wave voltammetry, were optimized. An overlapping of corresponding peaks of alpha-, gamma- and delta- form. The separation of oxidation signals was improved at optimum working conditions, but the signals were not completely resolved. However, it was found that this phenomenon did not cause significant changes in peak currents for various concentration ratios of tocopherols, which could be possibly utilized in analytical applications.
Možnosti simultánní voltametrické detekce tokoferolů v nevodných médiích
Keywords: Tocopherols; glassy carbon electrode; square wave voltammetry; food analysis; Tokoferoly; elektroda ze skelného uhlíku; square wave voltametrie; analýza potravin